Football Fans in Indonesia and Malaysia in the 2000s: Fanaticism, Conflict, and Friendship - Faishal Hilmy Maulida (Soshum: Jurnal Sosial dan Humaniora)
This study examines the interaction between football fans in Indonesia who identify with the Mania culture and football fans in Malaysia who identify with the Ultras culture. Similar to the political relationship between Indonesia and Malaysia, there are ups and downs in the relationship between football fans in both nations. This study attempts to provide an overview of the emergence of fanaticism, conflict, and amicable interactions among Malaysian and Indonesian football fans. This study uses historical research methods, the historical method consists of 4 steps namely; (1) heuristics; (2) verification; (3) interpretation; (4) historiography. The findings indicate that the industrialization of football influences the growth of obsessive football supporters in Indonesia and Malaysia. Football is also affected by the political tension between Indonesia and Malaysia. In conclusion, because of their common origin and comparable languages, football clubs in both countries are the starting point of the friendly relationship between fans of the game in Indonesia and Malaysia. Mania, the identity of the Indonesian football culture, and Ultras Malaya, the identity of the Malaysian football culture, have emerged as distinct cultures among football fans from the two nations. The harmony that often exists between fans of Indonesia and Malaysia started to alter as a result of the positive relationships that exist between fan bases at the club level, as demonstrated above by the friendship between Aremania (Indonesia) and UltrasSel (Malaysia).